Ethics: also for young people? Exploring the explicit imparting of ethics as a possible approach in social education - Terje Halvorsen (Scottish Journal of Residential Child Care)
This article deals with an approach by which ethics are imparted to young people by way of a written text. The theoretical basis for such an approach, the preparation of an adjusted text, and an initial evaluation are presented. After formulating a manuscript in which the wording and content are adjusted for young people, a sample of eight secondary school students have read and assessed the text. The examined approach is based on the belief that young people are able to acquire and apply theoretical knowledge in the field of ethics much in the same way as adults. Such an assumption challenge prevailing positions in cognitive psychology. The findings made in this pilot study indicate that an explicit imparting of ethics may provide a viable new approach in professional social education.